2010
DOI: 10.7589/0090-3558-46.4.1252
|View full text |Cite
|
Sign up to set email alerts
|

Morbillivirus Infection in a Wild Siberian Tiger in the Russian Far East

Abstract: ABSTRACT:We report the first documented case of morbillivirus infection in a wild, freeranging Siberian tiger (Panthera tigris altaica). The tigress entered a small village in the Russian Far East in an ambulatory but stuporous state with no apparent recognition or fear of humans. Her condition progressed rapidly with neurological signs, anorexia, and ultimately death. Histologic lesions included vacuolated to malacic white matter in the brain stem, cerebellum, and thalamus, with associated lymphocytic meningo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 8 publications
(7 reference statements)
0
36
1
1
Order By: Relevance
“…It has also been suggested that focal spread of CDV across the glia limitans from infected cells in the pia mater to neurons in the underlying brain parenchyma may provide an additional route of neuroinvasion in dogs (7,8). Meningoencephalitis is also a feature of CDV infection of other species, with distemper inclusion bodies observed in the meninges of infected foxes (21) and histological evidence of meningoencephalitis reported in black-footed ferrets and a Siberian tiger (33,45). While some morbilliviruses such as measles or rinderpest virus rarely spread to the CNS, meningoencephalitis has also been reported in seals and dolphins infected with phocine distemper and cetacean morbilliviruses, respectively (16,17,23).…”
Section: Discussionmentioning
confidence: 98%
“…It has also been suggested that focal spread of CDV across the glia limitans from infected cells in the pia mater to neurons in the underlying brain parenchyma may provide an additional route of neuroinvasion in dogs (7,8). Meningoencephalitis is also a feature of CDV infection of other species, with distemper inclusion bodies observed in the meninges of infected foxes (21) and histological evidence of meningoencephalitis reported in black-footed ferrets and a Siberian tiger (33,45). While some morbilliviruses such as measles or rinderpest virus rarely spread to the CNS, meningoencephalitis has also been reported in seals and dolphins infected with phocine distemper and cetacean morbilliviruses, respectively (16,17,23).…”
Section: Discussionmentioning
confidence: 98%
“…Mass vaccination of domestic dogs has been proposed as a strategy for protecting endangered wildlife in many areas (26,27), but concerns arise over its cost-effectiveness as a conservation tool within a potentially complex system, especially when the contribution of dogs to disease maintenance is uncertain (28). The implementation of mass dog vaccination programs in the Serengeti ecosystem since 1996, although driven largely by the need to control rabies (29), provides an opportunity to evaluate the impact of dog vaccination on CDV infection in both dog and wildlife populations.…”
Section: Significancementioning
confidence: 99%
“…Traditionally, CDV is well known to cause potentially lethal disease among members of Canidae, Mustelidae, and Procyonidae. Recently, CDV has been recognized as a cause of morbidity and mortality in large felids, such as lions (Panthera leo) in Tanzania's Serengeti National Park in 1994 [32]; lions, tigers (Panthera tigris), leopards (Panthera pardus), and a jaguar (Panthera onca) in North American zoos in 1991-1992 [3]; and one Siberian tiger (Panthera tigris altaica) in Pokrovka, Russia, in 2004 [31]. Furthermore, CDV infection also has been reported in many non-carnivorous species, including collared peccaries (Tayassu tajacu) in Arizona [2] and non-human primates (Macaca fuscata, Macaca fascicularis, Macaca mulatta) [24,30,34,39].…”
mentioning
confidence: 99%